Investigating the determinants behind advertisement-avoidance on social networking sites by Generation Z students in Durban, South Africa. - Richards, Tamsin (The IIE, 2020)
This study is a qualitative exploration of the factors that cause Generation Z individuals in Durban, South Africa, to avoid advertisements on social networking sites. Generation Z includes those born between 1996 and 2012 and delineates the most technologically advanced generation of individuals. Growing up surrounded by technology, these individuals have unprecedented capacities to avoid advertisements on social networking sites – which is problematic for marketers trying to target them. This study uncovered the determinants responsible for causing Generation Z to avoid advertisements on social networking sites, through the use of secondary research and a questionnaire – which allowed for an in-depth exploration of participants’ subjective determinants of advertisement-avoidance. It was concluded that goal impediment, scepticism, privacy concerns, advertisement clutter, pop-up, video- and engagement advertisements are relevant determinants that cause advertisement-avoidance among Generation Z. The reason that these determinants cause advertisement-avoidance is due to their great tendency to evoke negative emotions and perceptions among Generation Z individuals who engage with them. People’s attitudes towards advertisements are pivotal mediators in determining whether or not they engage with an advertisement – hence in determining an advertisement’s effectiveness. Recommendations have been made, in efforts to further reduce the gaps in this under researched phenomenon.
Keywords: Generation Z; Social media; Advertising; Advertisements; Social networking